Pathways of diffusion of some plants and animals between Asia and the Mediterranean region - Françoise Aubaile (Revue d'ethnoécologie)
Knowledge of the centres of origin of plants and animals has increasingly improved. However, it is much harder to identify the way through which plants and animals were distributed, by what roads and what means they arrived at one place or another, who brought them and who diffused them. Even for the most important and prestigious ones, many uncertainties persist. We cannot claim to resolve them, but we will present what is known to date about some major plants and animals, particularly the Asian ones that arrived in the Mediterranean region, and the other way, the ones that started in the Mediterranean and were diffused in the Far East.